2020
DOI: 10.1016/j.ejphar.2020.173553
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of chlorpromazine, fluphenazine, perphenazine, prochlorperazine, and thioridazine towards RNA-viruses. A review

Abstract: In 2020 the whole world focused on antivirus drugs towards SARS-CoV-2. Most of the researchers focused on drugs used in other viral infections or malaria. We have not seen such mobilization towards one topic in this century. The whole situation makes clear that progress needs to be made in antiviral drug development. The first step to do it is to characterize the potential antiviral activity of new or already existed drugs on the market. Phenothiazines are antipsychotic agents used previously as antiseptics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 50 publications
4
46
0
1
Order By: Relevance
“…Overall, the present analysis, together with other studies, 4,9,[66][67][68][69][70][71][72] supports our initial observation 2 and suggests that some psychiatric patients could have been protected by their pharmacological treatments. Along this line of reasoning, it should also be mentioned that these patients receive in general a cocktail of drugs (psychotropic and anti-histamine molecules) including several CAD compounds possibly working on different molecular mechanisms.…”
Section: Resultssupporting
confidence: 89%
“…Overall, the present analysis, together with other studies, 4,9,[66][67][68][69][70][71][72] supports our initial observation 2 and suggests that some psychiatric patients could have been protected by their pharmacological treatments. Along this line of reasoning, it should also be mentioned that these patients receive in general a cocktail of drugs (psychotropic and anti-histamine molecules) including several CAD compounds possibly working on different molecular mechanisms.…”
Section: Resultssupporting
confidence: 89%
“…Zuclopenthixol, the neuroleptic with the strongest association with sedation and somnolence, has emerged as a compound that shows in vitro inhibition of the severe acute respiratory coronavirus 2 (SARS-CoV-2) pathogen which causes the novel coronavirus disease 2019 (COVID-19) (Bocci et al, 2020). A recent review article reported thioridazine, fluphenazine, perphenazine, chlorpromazine, prochlorperazine inhibits RNA viruses as these phenothiazines inhibit cell-cell fusion, viral replication, clathrin-dependent endocytosis, and entry into cells (Otręba et al, 2020). Dyall and colleagues, reported FIGURE 1 | Forest plots illustrating reporting odds-ratios (RORs) with 95% confidence intervals (CI) of sedation and somnolence among all thirty-seven typical an atypical antipsychotic compounds.…”
Section: Study Findings and Recent Interests In Antipsychotic Drug Rementioning
confidence: 99%
“…Chlorpromazine, fluphenazine, and thioridazine are from the phenothiazine class of drugs with antipsychotic properties that are used in the treatment of schizophrenia and bipolar disorders [ 4 ]. Moreover, research from the last 15 years suggests that phenothiazines could play an important role in the treatment of other diseases: cancer as well as viral, bacterial, and fungal infections [ 5 , 6 , 7 , 8 ]. The anticancer activity of phenothiazines is related in part to reactive oxygen species (ROS) production, DNA fragmentation, and stimulation of apoptosis as well as inhibition of migration and invasiveness [ 5 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%